Failure to Rescue and Mortality Following Resection of Intracranial Neoplasms. Issue 2 (1st August 2017) - Malone, Hani; Cloney, Michael; Yang, Jingyan; Hershman, Dawn L; Wright, Jason D; Neugut, Alfred I; Bruce, Jeffrey N
Abstract: BACKGROUND: There is growing recognition that perioperative complication rates are similar between hospitals, but mortality rates are lower at high-volume centers. This may be due to differences in the ability to rescue patients from major complications. OBJECTIVE: To examine the relationship between hospital caseload and failure to rescue from complications following resection of intracranial neoplasms. METHODS: We identified adults in the Nationwide Inpatient Sample diagnosed with glioma, meningioma, brain metastasis, or acoustic neuroma, who underwent surgical resection between 1998 and 2010. We stratified hospitals by low, intermediate, and high surgical volume tertiles and calculated failure to rescue rates (mortality in patients after a major complication). RESULTS: A total of 550 054 patients were analyzed. Overall risk-adjusted complication rates were comparable between low- and medium-volume centers, and slightly lower at high-volume centers (15.3% [15.2, 15.5] vs 15.7% [15.5, 15.9] vs 14.3% [14.1, 14.6]). Risk-adjusted mortality decreased with increasing hospital surgical volume (10.3% [10.2, 10.5] vs 9.0% [8.9, 9.1] vs 7.1% [7.0, 7.2]). The overall risk-adjusted failure to rescue rate also decreased with increasing surgical volume (26.9% [26.3, 27.4] vs 24.8% [24.3, 25.3] vs 20.9% [20.5, 21.5]). CONCLUSION: While complication rates were similar between high-volume and low-volume hospitals following craniotomy for tumor, mortality rates were substantially lower at high-volume centers. This appears to be due to the ability of high-volume hospitals to rescue patients from major perioperative complications.